Development of slow electric field sensor in Legoland Malaysia resort - Ramli, Erman (2024)
Considering the industry's needs in general and LEGOLAND Malaysia Resort's specific requirements, LEGOLAND Malaysia Resort only required a short-range lightning detection system with a distance and radius of 7-8 km or less. This lightning information was needed to inform and warn visitors to move from open or wet areas to safe sheltered areas such as buildings or shade. Based on these requirements and considering the characteristics of the slow electric field, indeed it was deemed sufficient and suitable as a prediction method for LEGOLAND Malaysia Resort. This research pioneered a novel approach by delving into the analysis of the slow electric field, aiming to develop a waveform analysis to estimate the distance and radius of lightning occurrences at LEGOLAND Malaysia Resort. The newly implemented and installed Lightning Detection System (LDS) at LEGOLAND Malaysia Resort leveraged a straightforward and cost-effective setup, incorporating a capacitive antenna, slow and fast electric field sensors and dedicated data analysis software. In order to achieve accurate data, proper grounding and isolation from electrical noise were essential, as signal interference from power lines, towers or machinery could potentially trigger false signals. The effectiveness and accuracy of the LDS underwent a rigorous comparison with data from a weather service provider subscribed monthly by LEGOLAND Malaysia Resort, namely the Data Transmission Network (DTN), where lightning information from the DTN was sent to LEGOLAND Malaysia Resort via email. A comprehensive data set of approximately 50,000 lightning strikes was collected between July 2020 and July 2022. The analysis was made with a focus on December 2020 as the peak of the rainy and lightning season in Malaysia, showed that the LDS demonstrated superior lightning detection capabilities compared to DTN, identifying 69% of strike compared to DTN 31%. Negative Cloud-to-Ground (-NCG) lightning dominated the data, accounting for over 75% of all strikes at Legoland Malaysia Resort, Intracloud (IC) lightning represented 13%, while Narrow Bipolar Event (NBE) and Positive Cloud-to-Ground (+PCG) lightning comprised 5% and 2%, respectively. -NCG lightning was the most common type of cloud-to-ground lightning, accounting for about 70% of all lightning worldwide. Apart from that, 45% of lightning occurred Within the Reversal Distance (WRD), while the remaining 55% happened Beyond the Reversal Distance (BRD). This research contributed detailed documentation on the analysis of slow electric field data, encompassing waveform patterns and key characteristics. The comparative evaluation between the novel system and the current subscription service at LEGOLAND Malaysia Resort shed light on the efficiency and capabilities of the newly introduced methodology and served as a valuable resource for future research and refinement of lightning detection systems.